Identificación y evaluación de causas de accidentes de tránsito aplicando el método DREAM (Driving Reliability and Error Analysis Method) para proponer medidas preventivas en el distrito José Luis Bustamante Rivero - 2019 - Ccoya Cayra, Oriana Arelys (2019)
The gift objective of the research is identify to and evaluate the causes of traffic accidents by applying the DREAM method to propose preventive measures in the José Luis Bustamante Rivero District of the Province of Arequipa. First a data collection is performed, the critical points are identified where more accidents occur. Interviews designed to identify the phenotypes and genotypes of traffic eventualities will be applied to recognize where these accidents or more recurring eventualities come from and thus according to the data obtained to apply control measures. The analysis of causes of the accidents is given by conducting an evaluation of data collected at the police station and the data from the statistical bases. The evaluations on the causes mentioned above were carried out applying this DREAM method, which shows that traffic accidents are more misunderstanding or ignorance of signaling with 37.8%, poor estimation of intervals 36.01%, access limitations within the vehicle with 7.8%, Under the influence of substance with 7.1%, Vehicle failures 4.7% and the least uncommon cause is Sudden deterioration of health 1.7%. Due to the level high misunderstanding and ignorance traffic signals, measures were developed such as the preparation of an annual training program, Ludo prevention workshop and reminder to reduce traffic accidents that occur in José Luis Bustamante y Rivero.